The Politeness Strategy of Prophet Muhammad SAW in the Riyadhus Shalihin Book - Alwasilah, Yuzaki Adam (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
Language is, first and foremost, a means of communication; politeness may be one of the factors to consider. One of the aspects that worry Muslims is politeness. This study aimed to investigate the politeness speech acts of Prophet Muhammad SAW in the way he delivers his message to people who have less knowledge in Islam. This is a qualitative study and document analysis was used as a data collection technique in this study. The document of Riyadhus Shalihin book was analyzed and evaluated by the heuristics technique. The result shows that Prophet Muhammad SAW always shows politeness to respond to those who spoke rudely to him. Examining Prophet Muhammad SAW's use of positive and negative politeness strategies in response to impolite interactions with the public. Further research could explore the impact of these politeness strategies on conflict resolution and establishing harmonious relationships within a Muslim community.